2019
DOI: 10.1002/jsfa.9526
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofAngelica gigasNakai on the production of decursin‐ and decursinol angelate‐enriched eggs

Abstract: BACKGROUND The livestock industry requires high‐quality products, as well as improved productivity. There have been many studies regarding the utilization of feed additives aiming to increase productivity, enhance immune functions and prevent infectious diseases in livestock. Biofunctional feed additives would be beneficial not only for animal health, but also for consumers. In the present study, we utilized root and byproduct (stem and leaf) powders of Angelica gigas Nakai (AGN, Korean Danggui) as feed additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Generally, coumarin derivatives, such as decursin and its isomer, decursinol angelate, are the primary effective compounds isolated from the AGN plant and have attracted attention because of their numerous pharmacological effects (Cho et al, ; Hwang et al, ; Mahat et al, ). In the previous report, we found that the amounts of decursin and decursinol angelate in the stem and leaf of AGN were approximately one‐third of those in the root, indicating that, as byproducts, the stem and leaf could be utilized to provide supplementary bioactive material (Fontamillas et al, ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Generally, coumarin derivatives, such as decursin and its isomer, decursinol angelate, are the primary effective compounds isolated from the AGN plant and have attracted attention because of their numerous pharmacological effects (Cho et al, ; Hwang et al, ; Mahat et al, ). In the previous report, we found that the amounts of decursin and decursinol angelate in the stem and leaf of AGN were approximately one‐third of those in the root, indicating that, as byproducts, the stem and leaf could be utilized to provide supplementary bioactive material (Fontamillas et al, ).…”
Section: Discussionmentioning
confidence: 84%
“…In the previous report, we found that the amounts of decursin and decursinol angelate in the stem and leaf of AGN were approximately one-third of those in the root, indicating that, as byproducts, the stem and leaf could be utilized to provide supplementary bioactive material (Fontamillas et al, 2019).…”
Section: Fatty Acid Metabolismmentioning
confidence: 81%
See 1 more Smart Citation
“…The active component in A. gigas Nakai root extracts (ARE) is decursin or decursinol angelate. Purification or extraction of the active compounds may increase the efficacy of ARE 8 …”
Section: Introductionmentioning
confidence: 99%
“…Purification or extraction of the active compounds may increase the efficacy of ARE. 8 The importance of water as a material for functional is increasing, not only as a role of quenching thirst. Mineral-rich water is abundant in minerals and nutrients derived from volcanic rocks.…”
mentioning
confidence: 99%